Inspiratory Muscle Performance Is Significantly Related to Acceleration and Deceleration of Isokinetic Knee Extension and Flexion in Division 1 Collegiate Women Soccer Players: A Pilot Study - Tiffany Kasa; Luis A. Feigenbaum; Jeffrey T. Ruiz; Meryl Cohen; Julia L. Rapicavoli; Nicholas H. Dibble; Robert O. Poliszuk; Rebecca Jones; Lawrence P. Cahalin (Sci)
This study examines the relationship between inspiratory muscle performance (IMP) using the Test of Incremental Respiratory Endurance (TIRE), knee extension (EXT) and flexion (FLEX) acceleration (ACCEL) and deceleration (DECEL) times on an isokinetic dynamometer (ID), and performance of the Yo-Yo Intermittent Recovery Test Level 1 (YYIRT1) among thirteen Division I collegiate women soccer players (D1CWSP). Knee EXT and FLEX were tested at three velocities (60°/s, 180°/s, and 300°/s) using ID, while IMP was measured using maximal inspiratory pressure (MIP) and sustained maximal inspiratory pressure (SMIP). Significant negative correlations were found between MIP and the ACCEL time of FLEX at 60°/s and 300°/s, as well as between MIP and the DECEL time of EXT at 180°/s. Additionally, SMIP was negatively correlated with ACCEL times of FLEX at 180°/s and 300°/s and with DECEL times for both EXT and FLEX at 300°/s. These results suggest that greater IMP is linked to faster ACCEL and DECEL times in knee EXT and FLEX, indicating a role of IMP in enhancing muscle recruitment and performance. The only significant correlation with the YYIRT1 performance was observed between the YYIRT accumulated distance and the ACCEL time of FLEX at 180°/s. These findings highlight a physiological mechanism whereby IMP may contribute to improved dynamic muscle performance, though further research is needed to explore its implications for overall athletic performance.